Pendekatan Konseling dalam Meningkatkan Tanggung Jawab Pribadi Klien - Gusman Lesmana; Nur Ajizah Panjaitan; Rika Ayuni; Mega Natasya; Nurhaliza Nurhaliza; Wida Melani; Dian Hikmah Br Tarigan (Universitas 45 Surabaya, 2025)
Personal responsibility is a fundamental aspect in the development of psychologically healthy individuals, because it relates to the individual's ability to make decisions, manage behavior, and bear the consequences of every choice made. Reality counseling, developed by William Glasser, emphasizes the importance of personal responsibility as the core of effective and sustainable behavior change. This study aims to examine how the reality counseling approach can improve the client's personal responsibility through the application of choice theory and WDEP (Want, Doing, Evaluation, Planning) procedures. The method used is a literature review by analyzing various relevant scientific literature sources, both in the form of books and journal articles, related to reality counseling and the concept of personal responsibility. The results of the study show that reality counseling is effective in helping clients develop personal responsibility through the process of making the client aware that behavior is the result of individual choice, evaluating current behavior, developing a realistic plan of action, and building a commitment to implement it. The practical implications of this approach are relevant to be applied in educational, clinical, and community counseling settings to support positive and responsible behavior change.